Are men dominant? Evidence of differences between physical activity and quality of life among older adults in China - Chen, Mo; Chen, Shanping; Wu, Yuyan; Song, Di; Xie, Lijun; Shang, Yao; Chen, Zhiyi (Frontiers in Public Health, 2023)
At present, the aging population is one of China's basic national concerns, and physical exercise offers endless potential to cope with it. However, the life expectancy of men in China is generally lower than that of women, and the health status of older men is more worrying. Could it be that differences in physical exercise cause the difference in life expectancy between older men and women? This study analyzes the exercise regimen of older men and women and its influence on their quality of life. Approximately 200 respondents aged over 60 were investigated using the SF-36 and exercise questionnaires. Our findings revealed the following: (1) The scores of seven dimensions of life quality of older men were significantly lower than those of older women (p < 0.001), but there was no significant difference only in physiological function (p > 0.05); (2) The exercise frequency and persistence of older men were significantly lower than those of older women (p < 0.001), but there was no significant difference in exercise time (p > 0.05); and (3) All eight indices of quality of life of older men were positively correlated with the four indices of exercise (0.250 < R < 0.597). Our study offered the following conclusions: (1) The health of older men who lack physical exercise is poor. From the perspective of healthy aging, older men are a vulnerable group that deserves more attention. (2) Within an appropriate range, the more older men participate in physical activity programs, the more conducive they are to improved health. (3) This study focuses on promoting physical exercise for older adults and suggests organizing them to participate in sports activities as an important measure to promote healthy aging in China.